2019
DOI: 10.3390/w11081711
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nutrient and Stoichiometry Gradients on Microbial Assemblages in Erhai Lake and Its Input Streams

Abstract: Networks of lakes and streams are linked by downslope flows of material and energy within catchments. Understanding how bacterial assemblages are associated with nutrients and stoichiometric gradients in lakes and streams is essential for understanding biogeochemical cycling in freshwater ecosystems. In this study, we conducted field sampling of bacterial communities from lake water and stream biofilms in Erhai Lake watershed. We determined bacterial communities using high-throughput 16S rRNA gene sequencing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…The influences of changing landcover on adjacent aquatic ecosystems can usually be observed in the first place via responses of stream biofilms, which play an integral role in biogeochemical cycling in stream ecosystems through nutrient uptake, transfer of nutrients to higher trophic levels, and remineralization (Schiller et al, 2007;Battin et al, 2016;Stutter et al, 2020). Stream biofilms support complex microbial communities (Schiller et al, 2007;Battin et al, 2016), which are likely linked to watershed conditions because landcover controls the export of C, N, and P from terrestrial systems to streams (Erol and Randhir, 2013;Liu et al, 2019), potentially shifting in situ benthic biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…The influences of changing landcover on adjacent aquatic ecosystems can usually be observed in the first place via responses of stream biofilms, which play an integral role in biogeochemical cycling in stream ecosystems through nutrient uptake, transfer of nutrients to higher trophic levels, and remineralization (Schiller et al, 2007;Battin et al, 2016;Stutter et al, 2020). Stream biofilms support complex microbial communities (Schiller et al, 2007;Battin et al, 2016), which are likely linked to watershed conditions because landcover controls the export of C, N, and P from terrestrial systems to streams (Erol and Randhir, 2013;Liu et al, 2019), potentially shifting in situ benthic biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, module hubs and connectors were the keystone taxa which are crucial in maintain network structures and ecosystems stability. In PYL, Chlorophyta, Ochrophyta, and Ciliophora were the module hubs and connectors in the microeukaryotic networks, which were usually acted as the dominant phylum in many other lake and reservoir ecosystems [31,95]. Moreover, most of these module hubs and connectors were rare OTUs in PYL, suggesting that rare taxa can act as keystone taxa in the microeukaryotic networks, and the disappearance of these taxa could lead to the breaking apart of modules and networks [31].…”
Section: Discussionmentioning
confidence: 99%
“…Another study with a dataset covering a whole decade between 2004 and 2014 reported that cyanobacteria constituted up to 60% of the primary producer biovolume, with increased dominance after 2010 [18]. The importance of phosphorus management was showcased by Liu et al [12], not only for cyanobacteria control but also for the "satellite" bacterial communities of a eutrophic lake, which, in total, might affect the biogeochemical functioning of the whole lake.…”
Section: Contributionsmentioning
confidence: 99%
“…In this direction, a deeper understanding of the mechanisms that determine cyanobacterial bloom structure and toxin production become a target for managing practices [5,6]. This Special Issue, entitled "Advancing Knowledge on Cyanobacterial Blooms in Freshwaters", includes 11 research papers [9][10][11][12][13][14][15][16][17][18][19] and aims to bring together the recent research of multiand interdisciplinary approaches from the field to the laboratory and back again, driven by working hypotheses based on any aspect from ecological theory to applied research on mitigating cyanobacterial blooms.…”
Section: Introductionmentioning
confidence: 99%